Concomitant tumor and autoantigen vaccination supports renal cell carcinoma rejection - Herbert, Nicolás Nathaniel; Haferkamp, Axel; Schmitz-Winnenthal, Friedrich Hubertus; Zöller, Margot (The journal of immunology, 2010)
Efficient tumor vaccination frequently requires adjuvant. Concomitant induction of an autoimmune response is discussed as a means to strengthen a weak tumor Ag-specific response. We asked whether the efficacy of dendritic cell (DC) vaccination with the renal cell carcinoma Ags MAGE-A9 (MAGE9) and G250 could be strengthened by covaccination with the renal cell carcinoma autoantigen GOLGA4. BALB/c mice were vaccinated with DC loaded with MHC class I-binding peptides of MAGE9 or G250 or tumor lysate, which sufficed for rejection of low-dose RENCA-MAGE9 and RENCA-G250 tumor grafts, but only retarded tumor growth at 200 times the tumor dose at which 100% of animals will develop a tumor. Instead, 75-100% of mice prevaccinated concomitantly with Salmonella typhimurium transformed with GOLGA4 cDNA in a eukaryotic expression vector rejected 200 times the tumor dose at which 100% of animals will develop tumor. In a therapeutic setting, the survival rate increased from 20-40% by covaccination with S. typhimurium-GOLGA4. Autoantigen covaccination significantly strengthened tumor Ag-specific CD4+ and CD8+ T cell expansion, particularly in peptide-loaded DC-vaccinated mice. Covaccination was accompanied by an increase in inflammatory cytokines, boosted IL-12 and IFN-γ expression, and promoted a high tumor Ag-specific CTL response. Concomitant autoantigen vaccination also supported CCR6, CXCR3, and CXCR4 upregulation and T cell recruitment into the tumor. It did not affect regulatory T cells, but slightly increased myeloid-derived suppressor cells. Thus, tumor cell eradication was efficiently strengthened by concomitant induction of an immune response against a tumor Ag and an autoantigen expressed by the tumor cell. Activation of autoantigen-specific Th cells strongly supports tumor-specific Th cells and thereby CTL activation.
Gesehen am 19.04.2023